The right stuff [videorecording (DVD)] - Kaufman, Philip, 1936-; Kaufman, Philip, 1936-; Winkler, Irwin; Chartoff, Robert; Glenn, Scott, 1942-; Harris, Ed, 1950-; Hershey, Barbara, 1948-; Quaid, Dennis; Reed, Pamela; Shepard, Sam, 1943-2017; Stanley, Kim; Ward, Fred, 1942-2022; et al. (Warner Home Video, 2010)
The true story of Alan Shepard, Gus Grissom, John Glenn, Scott Carpenter, Walter Schirra, Gordon Cooper, and Deke Slayton -- the seven men chosen for the Mercury Project manned space flight program in the U.S.